Botulinum toxin in temporomandibular disorder (Research, Society and Development, 2023)
Daily challenges can trigger disturbances in the environmental, psychological, biological and cognitive domains, impacting systemic homeostasis and contributing to the emergence of disorders such as depression and anxiety. Patients exposed to such challenges have a higher incidence of disorders related to the temporomandibular joint (TMJ). The prevalence of temporomandibular disorder (TMD) has become recognized, with more than 100 million cases in the 1990s, resulting in the annual production of 3 million occlusal splints in the USA. Alternative approaches have been developed, offering comparable recovery rates. Symptoms associated with TMD include headache, ear pain, toothache, facial pain and tinnitus, often linked to psychological stress. Therapeutic success in TMJ is linked to a comprehensive plan, involving clinical and surgical approaches. Botulinum toxin (TxB) has seven forms, inhibiting the release of acetylcholine and inducing temporary muscle inactivity. Types A (TxB-A) and B (TxB-B) are applied clinically in specific areas. TxBo, type A, is effective in controlling muscle hyperactivity, especially when the origin of pain in TMD is myogenic. This review seeks to explore these interactions to provide a comprehensive overview of the therapeutic management of TMDs.